Maximum Extractable Value (MEV) Mitigation Approaches in Ethereum and Layer-2 Chains: A Comprehensive Survey - Zeinab Alipanahloo; Abdelhakim Senhaji Hafid; Kaiwen Zhang (IEEE Access)
Maximal Extractable Value (MEV) represents a pivotal challenge within the Ethereum ecosystem; it impacts the fairness, security, and efficiency of both Layer 1 (L1) and Layer 2 (L2) networks. MEV arises when miners or validators manipulate transaction ordering (e.g., front-running) to extract additional value, often at the expense of other network participants. This not only affects user experience by introducing unpredictability and potential financial losses but also threatens the underlying principles of decentralization and trust. Given the growing complexity of blockchain applications, particularly with the increase of Decentralized Finance (DeFi) protocols, it is crucial to address the issue and reduce the impact of MEV. This paper presents a comprehensive survey of MEV mitigation techniques as applied to both Ethereum’s L1 and various L2 solutions. We provide a novel categorization of mitigation strategies. We also describe the challenges, ranging from transaction sequencing and cryptographic methods to reconfiguring decentralized applications (DApps) to reduce front-running opportunities. We investigate their effectiveness, implementation challenges, and impact on network performance. By synthesizing current research, real-world applications, and emerging trends, this paper aims to provide a detailed roadmap for researchers, developers, and policymakers to understand and combat MEV in an evolving blockchain landscape.